2014
DOI: 10.1021/jp506039y
|View full text |Cite
|
Sign up to set email alerts
|

Free Volume Study on the Origin of Dielectric Constant in a Fluorine-Containing Polyimide Blend: Poly(vinylidene fluoride-co-hexafluoro propylene)/Poly(ether imide)

Abstract: The dielectric constant of fluorinated polymides, their blends, and composites is known to decrease with the increase in free volume due to a decrease in the number of polarizable groups per unit volume. Herein, we report an interesting finding on the origin of dielectric constant in a polymer blend prepared using a fluorine-containing polymer and a polyimide probed in terms of its available free volume, which is distinct from the generally observed behavior in fluorinated polyimides. For this study, a blend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…Thus, this change is attributed to the dielectric relaxation of PVH on passing its T g . Our recent free volume study on PVH reveals that the dielectric constant in PVH arises mainly due to dipole orientation polarization . Below −40 °C, the PVH is in the glassy phase and hence the molecular motions are frozen in place due to which the dipoles cannot move to align themselves to the applied electric field.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, this change is attributed to the dielectric relaxation of PVH on passing its T g . Our recent free volume study on PVH reveals that the dielectric constant in PVH arises mainly due to dipole orientation polarization . Below −40 °C, the PVH is in the glassy phase and hence the molecular motions are frozen in place due to which the dipoles cannot move to align themselves to the applied electric field.…”
Section: Resultsmentioning
confidence: 97%
“…The corresponding dielectric loss is also high [see Figure (E)]. The glass transition temperature ( T g ) of PVH is −33 °C . Thus, this change is attributed to the dielectric relaxation of PVH on passing its T g .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain low‐dielectric PI, two strategies are mainly used: (1) decreasing dipole strength or (2) reducing the number of dipoles . It has been reported that the introduction of fluorine atoms into the PI backbone could reduce D k and improve water resistance .…”
Section: Introductionmentioning
confidence: 99%
“…synthesized perfluorocyclobutyl biphenyl ether‐based PI, which showed low D k (2.43−2.50) upon moisture absorption for 24 h. However, this kind of PI suffers from poor adhesion with metal. Because the D k of air is approximately 1.0, introducing air voids into PI will decrease the dielectric permittivity of PI . These PIs, such as nanoporous PI and PI aerogels, have been extensively studied .…”
Section: Introductionmentioning
confidence: 99%